Integrated medical and nursing ward rounds in a patient with gastrointestinal dysfunction after gastric cancer surgery (1例胃癌术后胃肠功能紊乱患者的医护一体化查房) - ZHAO Yan (赵燕); LIU Shuhong (刘书红); TANG Ling (唐玲); LI Ye (李野); E Haiyan (鄂海燕) (中西医结合护理)
To summarize the application effect of integrated medical and nursing ward rounds in a patient with gastrointestinal dysfunction after gastric cancer surgery. Based on the integrated medical and nursing ward rounds model, the evaluation was carried out by using quantitative table. The application of the integrated ward round mode is conducive to promoting the postoperative recovery, alleviating the pain, reducing the occurrence of complications and improving the quality of life of the patient. (总结1例胃癌术后胃肠功能紊乱患者的医护一体化查房实施经验。以医护一体化查房模式为主导, 采用量化表进行评价。该模式有利于促进患者胃肠功能恢复, 减轻患者痛苦, 减少并发症的发生, 提高患者生活质量。)